IMPLEMENTASI STRATEGI DISKUSI PADA MATA PELAJARAN AL-QUR’AN HADIST DI MI MIFTAHUL ULUM KOTA BATU - Dinda Aulia Fitri; Devi Wahyu Ertanti; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The problem in this research is the strategy used in the learning process is still not going well and the strategies used by the teacher have not run optimally. The research was conducted at MI Miftahul Ulum Jl. Dorowati, Sisir, Kota Batu. Data collection procedures are carried out using observation, interview and documentation methods. From the research activities on students understanding of the material Al-Qur’an Hadith are some students still can not understand the material because the verses taught are too long, the implementation of discussion strategies on the subjects of the Al-Qur'an Hadith at MI Miftahul Ulum Kota Batu, covering the preliminary activities the teacher gives murottal, ice breaking and quizzes, at the core activity, the teacher implements based on the applicable curriculum namely observe, ask questions, explore, associate and communicate, and in closing activities teachers conduct evaluation and reflection activities. Regarding the obstacles in the use of discussion strategies namely the limited hours of learning, students who have not read fluent letters and students who do not dare express their opinions.